Aplastic anemia in a patient with papillary thyroid carcinoma complicated with Hashimoto’s thyroiditis: a case report - Fei Wu; Yiwei Xiao; Rui Hai; Xiaodong Chen; Shanshan Liu; Xiangyu Zhou (Frontiers in Oncology)
BackgroundIt is uncommon to come across instances of aplastic anemia in individuals suffering from papillary thyroid carcinoma complicated by Hashimoto’s thyroiditis. Here, a unique case is presented.Case presentationA 23-year-old male was admitted to the hospital for “a lump in his right neck”. Laboratory tests revealed a decrease in white blood cells (WBC), red blood cells (RBC), and platelet count (PLT). Bone marrow aspiration revealed an extremely low degree of hyperplasia of hematopoietic cells. Simultaneously, the levels of thyroglobulin antibodies and thyroid peroxidase antibodies were significantly elevated. Neck ultrasound findings revealed nodules in both lobes of the thyroid. Moreover, fine-needle aspiration biopsy indicated the atypical presence of proliferative thyroid epithelial cells. Even after implementing various treatments hematopoietic function could not be restored. However, following a surgery, the patient’s WBC, RBC, and platelet counts gradually returned to normal.ConclusionsHere, we present a case that thyroid cancer complicated with Hashimoto’s thyroiditis may affect hematopoietic function.